In situ Photosynthetic Activities and Associated Biogeochemical Changes in Three Tropical Seagrass Species - Purvaja, Ramachandran; Ganguly, Dipnarayan; Hariharan, G.; Arumugam, K.; Ramesh, R. (Frontiers in Earth Science, 2020)
Tropical seagrasses experience considerable spatio-temporal changes with light and other biogeochemical conditions and adopt species-specific acclimatization strategies. Variation in photo-acclimatory responses of three tropical seagrass species (Cymodocea serrulata, Thalassia hemprichii, and Enhalus acoroides) was studied by measuring photosynthetic electron transport rates (ETR) using Pulse Amplitude Modulated (PAM) fluorometry. Quantitative values of ETR and rates of photosynthetic O2 evolution (net O2 exchange corrected for dark respiration) were compared to establish species-specific relationships in shallow water conditions. The apparent average molar ratio of O2 evolution to ETR for the studied species found lower than the theoretical value (0.25). The highest photosynthetic activity (ETRmax) varied significantly among the three studied species in the decreasing order as: E. acoroides (59.27); T. hemprichii (54.06), and C. serrulata (46.72). The effective quantum yield (Y) of PS II (Photosystem II), one of the most useful indicators of stress conditions for seagrass, was observed to be significantly higher for E. acoroides compared to the other two species. It appears that the variations in water temperature and pCO2 could significantly alter the photosynthetic characteristics of these shallow water seagrass species. This study is useful in predicting the photo-acclimation strategies to any change in light availability and subsequent biogeochemical changes at the sea bed by these tropical seagrass species.